Senescence-associated secretory phenotype regulation by dual drug delivery biomimetic nanoplatform for enhanced tumor chemotherapy - Anni Wang; Shiyi Li; Ru Zhang; Xing Chen; Ying Zhu; Jiaxuan Xia; Jianxin Wang (Molecular Therapy: Oncology)
Many chemotherapies, which are still the main clinical treatment for primary tumors, will induce persistent DNA damage in non-tumor stromal cells, especially cancer-associated fibroblasts (CAFs), and activate them to secrete senescence-associated secretory phenotype (SASP). The transition could further result in the formation of tumor immunosuppressive microenvironment and cause drug resistance of neighboring tumor cells. To solve this dilemma, a multi-functional biomimetic drug delivery system (named mPtP@Lipo) was rationally developed by combining CAFs reshaper ginsenoside 20(S)-protopanaxadiol (PPD) and cisplatin prodrug (PtLA) to inhibit tumor progression and the formation of SASP. To achieve effective delivery of these molecules deep into the desmoplastic tumor, fibroblast membrane was fused with liposomes as a targeting carrier. In vitro and in vivo results showed that mPtP@Lipo could penetrate deep into the tumor, reverse CAFs phenotype and inhibit SASP formation, which then blocked the immunosuppressive progress and thus reinforced anti-tumor immune response. The combination of chemotherapeutics and CAFs regulator could achieve both tumor inhibition and tumor immune microenvironment remodeling. In conclusion, mPtP@Lipo provides a promising strategy for the comprehensive stromal-desmoplastic tumor treatment.